(untitled) - bis 2017 herausgegeben von Prof. Dr. Joachim Jens Hesse (1942-2018) (ZSE Zeitschrift für Staats- und Europawissenschaften | Journal for Comparative Government and European Policy, 2013)
The quarterly Journal for Comparative Governement and European Policy is not only an outstanding multi-lingual and interdisciplinary journal but also a discussion forum for leading scientists and opinion makers from politics, culture and economy. It provides information on the key questions of public action at the European, the national and the regional level. The journal addresses legal and social scientists, historians and practitioners in politics and administration. Website: www.zse.nomos.de